Peran Perawat dan Bidan terhadap Pelaksanaan Inisiasi Menyusu Dini (IMD) - Bekti Sukoco; Endah Purwanti; Ade Ragil Agung Wibowo; Devvyta Ferika Sari (Jurnal Keperawatan Silampari, 2021)
This study aims to see how the role of officers in the implementation of early initiation of breastfeeding (IMD) and coverage of IMD in newborns. The method used is quantitative with a descriptive analysis approach. The results showed that the role of nurses and midwives in the implementation of IMD was included in the category with the mean score of 95.39. The IMD success rate is also included in the high category with an average score of 93.75. In conclusion, the role of nurses and midwives in the implementation of IMD is in the good category and the success of IMD is also in the high category. Keywords: Mother's Milk, Early Initiation of Breastfeeding, Role of Nurses and Midwives